2019
DOI: 10.1186/s12872-019-1165-5
|View full text |Cite
|
Sign up to set email alerts
|

Indirect comparison of novel Oral anticoagulants among Asians with non-Valvular atrial fibrillation in the real world setting: a network meta-analysis

Abstract: Background The development of novel oral anticoagulants (NOACs) has changed the landscape of non-valvular atrial fibrillation (NVAF) management. In this study, the effectiveness and the safety of several NOACs were evaluated in a real-world setting among Asian patients with NVAF. Methods The literature search was conducted crossing different databases including Embase, MEDLINE, and the Cochrane Library from inception through March 1, 2019, for studies which included rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
(39 reference statements)
3
9
0
2
Order By: Relevance
“…For this study we specifically were concerned with hospital readmission outcomes, but our findings between the warfarin and apixaban cohorts and the rivaroxaban and apixaban cohorts provide further evidence that apixaban treatment may be associated with better clinical outcomes than these other OACs. These findings are aligned with those of several real-world evidence studies [9][10][11][12][13][14][15][16][17][18][19] , as well as network meta-analyses of clinical trial data 23,24 , in which all have generally found apixaban to have the better safety profile (i.e. lowest bleeding risk) compared to other OACs.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…For this study we specifically were concerned with hospital readmission outcomes, but our findings between the warfarin and apixaban cohorts and the rivaroxaban and apixaban cohorts provide further evidence that apixaban treatment may be associated with better clinical outcomes than these other OACs. These findings are aligned with those of several real-world evidence studies [9][10][11][12][13][14][15][16][17][18][19] , as well as network meta-analyses of clinical trial data 23,24 , in which all have generally found apixaban to have the better safety profile (i.e. lowest bleeding risk) compared to other OACs.…”
Section: Discussionsupporting
confidence: 84%
“…A network meta-analysis published in 2018 of 11 studies conducted in the real-world setting has summarized that, of the OACs (warfarin, dabigatran, rivaroxaban, and apixaban), apixaban is associated with the lowest risk for MB (apixaban vs warfarin hazard ratio [HR] ¼ 0.58; 95% confidence interval [CI] ¼ 0.48-0.69; apixaban vs dabigatran HR ¼ 0.73; 95% CI ¼ 0.61-0.87; apixaban vs rivaroxaban HR ¼ 0.55; 95% CI ¼ 0.46-0.66) 15 . Directionally consistent results in regard to bleeding outcomes have been reported in other meta-analyses of real-world data [16][17][18][19] .…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…A better safety profile was found with apixaban compared with warfarin. 8,9 In the ARISTOTLE trial subgroup analyses, adjusted reduced dose of 2.5 mg twice a day (b.i.d.) of apixaban was as effective as warfarin for stroke prevention, and was associated with lower bleeding.…”
mentioning
confidence: 99%
“…Finally, anticoagulation decisions must take the higher intracranial haemorrhage rates of Indigenous Australians into account . Treatment with NOACs may be safer than with warfarin, as trials in Asian populations with similarly high intracranial haemorrhage risk have found that their rate is reduced by about 50% in patients receiving NOACs . Unfortunately, evidence about the safety of NOACs for Indigenous Australians is scarce.…”
mentioning
confidence: 99%